Using Light Scattering to Screen Polyelectrolytes (PEL) Performance in Flocculation - Rasteiro, Maria G. (2011)
Flocculation of precipitated calcium carbonate (PCC) was monitored using light diffraction spectroscopy (LDS). Four cationic polyacrylamides of high molar mass and with different degrees of branching, all copolymers of acrylamide (AM) and acryloyloxyethyltrimethyl ammonium chloride (Q9), were tested. LDS supplied information about the kinetic curves for flocs growth and also for the flocs structure evolution. Flocculation kinetics, flocs size and structure, flocs resistance and reflocculation capacity could be correlated with the degree of branching of the polyelectrolytes (PEL). Furthermore, PEL with different degrees of branching corresponded to different values for the intrinsic viscosity, indicating differences in the polymer conformation, which explained well the performance differences in flocculation.